2020
DOI: 10.1002/rcs.2097
|View full text |Cite
|
Sign up to set email alerts
|

Augmented reality for narrow area navigation in jaw surgery: Modified tracking by detection volume subtraction algorithm

Abstract: Background and Aim: Jaw surgery based on augmented reality (AR) still has limitations in terms of navigating narrow areas. Surgeons need to avoid nerves, vessels, and teeth in their entirety, not just root canals. Inaccurate positioning of the surgical instrument may lead to positional or navigational errors and can result in cut blood vessels, nerve channels, or root canals. This research aims to decrease the positional error during surgery and improve navigational accuracy by reducing the positional error.Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 27 publications
(67 reference statements)
0
5
0
Order By: Relevance
“…Basnet et al, (2018) proposed an augmented reality-based surgery system that improves navigation accuracy by eliminating noise and obstruction when the implant is placed about the jawbone to be cut or drilled. Furthermore, in jaw surgery, the AR system for narrow-area navigation has been proposed to reduce positional error within the surgery and increase navigational accuracy by positional error reduction (Budhathoki et al, 2020). In addition, Murugesan et al (2018) proposed a system applied in Oral and Maxillofacial Surgery (OMS) focusing on AR regarding geometric accuracy.…”
Section: Research Scopementioning
confidence: 99%
See 2 more Smart Citations
“…Basnet et al, (2018) proposed an augmented reality-based surgery system that improves navigation accuracy by eliminating noise and obstruction when the implant is placed about the jawbone to be cut or drilled. Furthermore, in jaw surgery, the AR system for narrow-area navigation has been proposed to reduce positional error within the surgery and increase navigational accuracy by positional error reduction (Budhathoki et al, 2020). In addition, Murugesan et al (2018) proposed a system applied in Oral and Maxillofacial Surgery (OMS) focusing on AR regarding geometric accuracy.…”
Section: Research Scopementioning
confidence: 99%
“…With other proposed systems by (Murugesan et al (2018), (Shrestha et al, 2021), (Budhathoki et al, 2020), (Bayrak et al, 2020), and (Manohar et al, 2020) the CT data of the patients were taken and then have been segmented. Subsequently, a hierarchy model is created.…”
Section: Pre-operative Phasementioning
confidence: 99%
See 1 more Smart Citation
“…The concept of AR has found wide application in the arts, gaming industry, architecture, daily life, industrial design, navigation, auto industry, archeology. With increased need for catheterization and endoscopic interventions, AR has found an important role in many medical disciplines (36) (Figure 5) (37)(38)(39). In dental education, it is increasingly used in everyday clinical practice and education.…”
Section: Virtual Reality and Augmented Realitymentioning
confidence: 99%
“…They compared the navigation method to physician's experience and concluded that AR guidance had better outcomes in terms of mean target error and mean angle error. Budhathoki et al (2020) emphasized the use of AR navigation to visualize deep-seated anatomy, narrow areas and to provide positioning of surgical instruments to avoid positioning error complications during jaw surgery. Moreover, Gao et al (2019) employed AR in mandibular split osteotomy.…”
mentioning
confidence: 99%